3PL selection using hybrid model of AHP-PROMETHEE. (1st January 2013) - Bansal, Ankit; Kumar, Pravin
This research paper aims to give a new dimension to the decision maker by proposing a hybrid model of analytic hierarchy process (AHP) and preference ranking organisation method for enrichment evaluation (PROMETHEE) in 3PL selection. It uses an integrated approach of AHP-PROMTHEE as a selection methodology to select an efficient and requisite 3PL firm for a manufacturer. A relatively new and user interactive software, visual PROMETHEE has been used to solve the problem. The hybrid model of AHP-PROMETHEE is a sound technique for 3PL selection. AHP easily performs the cumbersome process of weighting diverse criteria, whereas PROMETHEE ranks various alternatives according to their performance on the basis of these criteria. Application of hybrid model of AHP-PROMETHEE is an important tool for multi-criteria decision making (MCDM). Further research work on this method and its variants like fuzzy AHP and PROMETHEE VI may enlighten a new path for the decision makers. Moreover development of accurate and user-friendly software may prove very helpful in the selection process. However, types of criteria, their number and their importance may vary from firm to firm. So, it becomes extremely difficult to generalise the view of the 3PL selection process.